A computerized approach to group discussion and decision making - Motlagh, Omid Reza Esmaeili; Tang, Sai Hong; Ramli, Abdul Rahman; Ismail, Napsiah (Faculty of Educational Studies, Universiti Putra Malaysia, 2010)
Today, collaborative learning in high-tech institutions is not limited to supply of material by instructors and merely its consumption by students. Instead, learning is viewed as a cooperative task involving group discussions and analysis of the supplied information. Group discussion takes different forms starting from primary school activities till collaborative research and development projects in universities. On the basis of this idea, this paper introduces a practical computerized model for analyzing different viewpoints of a group of individuals on a specific decision problem or a single fact of knowledge. The results are presented using an example of a decision problem including 10 factors where 3 decision makers discuss to reach a consensus over the finalized values of the factors.